2016
DOI: 10.1074/mcp.m115.055376
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a Dual Regulatory Role for Caspases During Endoplasmic Reticulum Stress-induced Cell Death

Abstract: Many diseases are associated with endoplasmic reticulum (ER) stress, which results from an accumulation of misfolded proteins. This triggers an adaptive response called the “unfolded protein response” (UPR), and prolonged exposure to ER stress leads to cell death. Caspases are reported to play a critical role in ER stress-induced cell death but the underlying mechanisms by which they exert their effect continue to remain elusive. To understand the role caspases play during ER stress, a systems level approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…A very recent study showed that ZVAD-FMK also inhibited ER stress. Furthermore, it has been demonstrated in the same study that ER stress downregulated many caspase substrates at the protein level; caspases influenced ER stress pathway both by directly cleaving its substrates and also by deactivating transcription factors essential for upregulation of genes involved in cell fate decisions 58 .…”
Section: Discussionmentioning
confidence: 93%
“…A very recent study showed that ZVAD-FMK also inhibited ER stress. Furthermore, it has been demonstrated in the same study that ER stress downregulated many caspase substrates at the protein level; caspases influenced ER stress pathway both by directly cleaving its substrates and also by deactivating transcription factors essential for upregulation of genes involved in cell fate decisions 58 .…”
Section: Discussionmentioning
confidence: 93%
“…These functional differences are particularly evident in apoptosis, where some cleavage events drive apoptosis through gain-of-function, such as the activation of caspases themselves, whereas most of the cleaved substrates, such as inhibitor of the caspase-activated DNAse (ICAD), have undergone a loss-of-function. 54 For example, Anania et al 55 used a systems-level approach combining transcriptomics, proteomics, and N-terminomics to study the role of caspases during the unfolded protein response caused by endoplasmic reticulum stress. This study showed that caspase activation not only controls post-translational protein expression of direct caspase substrates, but also regulates transcription of genes involved Rank order in cell fate decisions in response to endoplasmic reticulum stress.…”
Section: Biochemistrymentioning
confidence: 99%
“…Therefore, we set up a TMT-compatible version of iNrich by replacing acetic anhydride with TMT and validated the method via a quantitative analysis of HCT116 cells treated with TM or TG (Figure A). The two reagents are known to induce ER stress and consequently a cellular response to the stress of unfolded proteins or unfolded protein response (UPR) . Using a 6-plex TMT reagent, 100 μg proteins of cells treated with TG, TM, and DMSO for 0 and 48 h, respectively, were labeled, and the iNrich-enriched N-terminomes were analyzed.…”
Section: Resultsmentioning
confidence: 99%